Promotion Strategy in Increasing Customer Loyalty in Companies - Sitindaon, Natanael; Lubis, Nurul Wardani; Malau, Grace Theresia; Siburian, Kristina Mesya Yulianti; Ayuningrum, Utrie Sekar (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This study aims to analyze the effect of promotional strategies on customer loyalty in companies. Customer loyalty is very important for business sustainability because loyal customers not only provide recurring income but also support promotions through word-of-mouth recommendations. This study uses a qualitative approach with a literature study method, where data is collected from various scientific sources that discuss promotional strategies and customer loyalty. Thematic analysis is used to identify key themes from relevant literature. The results of the study indicate that promotional strategies that include emotionally appealing advertising, sales promotions that provide real value, and personalized direct marketing can increase customer loyalty. In addition, good public relations and personal selling play a role in strengthening relationships with customers, thereby increasing brand trust. The implication of this finding is that companies need to design effective and targeted promotional strategies to build and maintain long-term customer loyalty, by considering emotional factors and relevance in each promotion.